2014
DOI: 10.1016/j.ijscr.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of colorectal recurrence of gastric cancer more than 5 years after primary resection

Abstract: INTRODUCTIONIntestinal metastasis from gastric cancer is rare, although the most common cause of secondary neoplastic infiltration of the colon is gastric cancer. However, little data is available on recurrence or death in patients with gastric cancer surviving >5 years post-gastrectomy. Here we report two cases of lower intestinal metastasis from gastric cancer >5 years after primary resection and discuss with reference to the literature.PRESENTATION OF CASECase 1: A 61-year-old man with a history of total ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Colonic metastasis of gastric cancer is rare and has been reported only occasionally in the literature [ Table 1 ]. 6 10 The characteristics of the case in this study were as follows: 1. The pathological diagnosis of specimens from the five surgeries was poorly differentiated adenocarcinoma containing components of signet ring cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic metastasis of gastric cancer is rare and has been reported only occasionally in the literature [ Table 1 ]. 6 10 The characteristics of the case in this study were as follows: 1. The pathological diagnosis of specimens from the five surgeries was poorly differentiated adenocarcinoma containing components of signet ring cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, surgical resection is necessary to control severe symptoms and ameliorate the quality of patients’ life. [ 25 ] We considered the operation for the sake of relieving the symptoms of hematochezia and abdominal distention caused by lumen stenosis of colon and improving the quality of life as well. And with the development of molecular targeted therapies and immunotherapies, VEGFR-2 inhibitors and PD-1 antibodies could also provide a good choice for the treatment of gastric carcinoma with HER-2 negative status.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al found the two-year cumulative survival rates to be significantly better for resection of the recurrence plus chemotherapy than for chemotherapy only (23.8% vs. 1.2%, p < 0.001) [2]. Other studies also report generally longer survival time when surgery is performed along with chemotherapy [5,6]. For any given patient, appropriateness of extensive resection should be assessed by a multidisciplinary assessment team.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent tumour develops in most cases and often makes gastric cancer incurable [2][3][4]. Recurrences after curative resection for gastric carcinoma have been categorised as locoregional recurrence, peritoneal recurrence, and distant (including haematogenous) metastasis [5]. Although there is no clear consensus on the treatment of choice for recur-rent gastric cancer, there have been a few reports on the relative effectiveness of surgical treatment in selected patients [6].…”
Section: Introductionmentioning
confidence: 99%